A HOLISTIC OVERVIEW: INDONESIA’S GEOTHERMAL ENERGY ENCOURAGES GEOTHERMAL POWER PLANT INVESTMENT IN SUPPORT OF NATIONAL DEFENSE - Azmi, Ulul; Sasongko, Nugroho Adi; Murtiana, Sri; Yanto, Sri; Saputro, Guntur Eko; Laksmono, Rudy; Supriyadi, Imam (Jurnal Pertahanan dan Bela Negara, 2024)
The Pacific Ring of Fire passes across Indonesia physically, and the country’s intense volcanic and tectonic activity has produced a wealth of geothermal resources that could reach 23,46 GW, distributed over 357 sites. To promote the decarbonization of Indonesia’s electricity supply and the advancement of geothermal energy, the Indonesian government issued Presidential Regulation No. 112/2022 on the Acceleration of Renewable Energy Development for Electricity Supply in 2022. To incentivize GPPs to invest, the lack of bids in PLN’s most recent procurement from 2021 requires more than the maximum electricity tariff. Investing in geothermal projects has some regulatory obstacles in addition to cost concerns. This study aims to assess geothermal investment in Indonesia and reduce reliance on fossil fuels, which are susceptible to price and supply volatility. GPPs ensure a consistent energy supply for national needs to support national defense. The method used is descriptive qualitative, which relies on literature studies that discuss appropriate issues. The National Energy Management Blueprint 2006-2025 presents the survey results. The Government of Indonesia plans geothermal energy to contribute about 5% of the national energy mix or about 7,32 GW in 2025. However, the realization of installed geothermal power plant capacity in 2023 only reached 2,38 GW, or 32,52 percent of the planned capacity to be installed. Through the Ministry of Energy and Mineral Resources, the government needs to increase the purchase price of electricity from IPP GPPs to create a good investment climate and continue to grow the geothermal industry.